Design, fabrication and performance evaluation of a hot air heating system for processing Malaysian cockles - Yavari, Iraj (2014)
Heat and the heating process are of the most widespread and the most important activities in the post-harvest operations for food products in the world. Such activities are usually expected to decrease the moisture content for crop preservation;the heating process is also used for modifying the mouthfeel of a product in order to raise the food‟s market values. Likewise, recovery and storage of the energy,environmental protection alongside the climate effect are considered as notable issues. Nowadays different types of heating system such as the hot air heating machines are being used for heating the food products. Mostly, fossil fuel has been used by machines for this purpose, making the heat energy in the direct combustion. The heat from burning fuels is supplied directly by the airflow through the blower housing and harmful gases directed to enter the food chamber and the environment. , It must also kept in mind that in a direct in- line burner using natural gas, 3.5 lb. of water is add to the air for every cubic meter of natural gas consumed . This action leaves undesirable and unintended effects on the product quality. Regarding these cases, such as non-constantity of the temperature in the compartment space of the products, lack of a precise temperature control, food contamination through contact with invisible gases from the burning fuel, more pollution and other environmental issues are among the disadvantages of these types of machines. Currently, the same actions are being used in Malaysia. Therefore, a new hot air heating system was required for heating the food and it‟s products having high capacity and satisfactory heating quality with no damage to the food quality and the environment. Air distribution in the machine reservoir and the flow rate were calibrated to achieve good results and outcomes in the construction phase as well as in the procedural steps to create the machine. To conserve energy, a closed circuit system and series was added to the machine. In this research work first, the parts of the machine were designed using CATIA software then new heating system based on a hot water recirculation technique and effective air velocity has been fabricated. An adjustable system was used to provide hot water with a high setting range of adjustment and high precision for different temperatures up to ninety degrees at the constant pressure. In order to avoid energy losses and prevent pollution of the environment A Newly Developed and Extra-Enclosed System was designed, fabricated and add to the machine. For this purpose two extra devices of heat exchanger mounted on the machine, one located at the blower fan inlet and other situated at the air outlet final channel of machine. Both energy saving heat exchangers have been connected by connecting series and insulated tubes. The new machine was tested in the Agricultural Process and Instrument Laboratory (APIL) of the faculty of engineering in UPM. The tests were performed based on the Randomized Complete Block Design (RCBD) experimental design was with three replications and the means were being compared using the Duncan‟s Multiple Range Test (DMRT). The parameters included the air temperature at three levels, the air velocity at three levels, and the hot air heting time duration at five levels. The data measured included the energy consumption, the opening force of the cockle shells, the moisture content, the cutting force, the compression force, the penetration force,the meat volume, the length, the height, the inflation, and the air and water temperature profiles. The Malaysian cockle (Anadara Granosa L.) was used as the experimental material. The results revealed that the best and lowest cockle‟s opening force [N] belonged to the hot air heating parameters (air velocity: 2 m/s, air temperature: 70 °C) in the first hours of process, [M=(111±6.4) ×10-2][N]. For the volume of the cockle‟s, the best result was observed at (air velocity: 2 m/s, air temperature: 70 °C) in the first hours of the air heating time [M =(3.47± 0.19)] [cm3]. Results also showed that the lowest MC- % happened at (air velocity:1 m/s, air temperature: 50 °C) after 1hour (M=0. 26%± 0.01). The best treatment on the cutting stress (τ, N/m2) was at the air parameter of (air velocity: 1 m/s, air temperature: 60 °C) in the first hours of the experiment [M= (1.08±0.02) ×105] [N/ m2]. The lowest penetration force [N], was also observed for the air parameter of (air velocity:1m/s, air temperature: 50 °C) in the first hours of time duration [M=(52± 0.58) ×10-2] [N]. The lowest compression stress (σ, N/m2) was observed for the air parameter of (air velocity: 1 m/s, air temperature: 50 °C) in the first hours [M=(0.7887± 0.004) ×105][N/m2]. For the boiling experiment, it was found that the opened cockle, the cutting stress, the penetration force, and the compression stress increased significantly by having an increase in the boiling time. In this test, by increasing the boiling time, the cockle‟s volume decreased significantly and the lowest volume was for 15 min of boiling [M=(2.033± 0.033)] [cm3].